Bacteria contribute to plant secondary compound degradation in a generalist herbivore system. - Francoeur, Charlotte B. (2020)
Herbivores must overcome a variety of plant defenses, including coping with plant secondary compounds (PSCs). To help detoxify these defensive chemicals, several insect herbivores are known to harbor gut microbiota with the metabolic capacity to degrade PSCs. Leaf-cutter ants are generalist herbivores, obtaining sustenance from specialized fungus gardens that act as external digestive systems and which degrade the diverse collection of plants foraged by the ants. There is in vitro evidence that certain PSCs harm Leucoagaricus gongylophorus, the fungal cultivar of leaf-cutter ants, suggesting a role for the Proteobacteria-dominant bacterial community present within fungus gardens. In this study, we investigated the ability of symbiotic bacteria present within fungus gardens of leaf-cutter ants to degrade PSCs. We cultured fungus garden bacteria, sequenced the genomes of 42 isolates, and identified genes involved in PSC degradation, including genes encoding cytochrome P450 enzymes and genes in geraniol, cumate, cinnamate, and alfa-pinene/limonene degradation pathways. Using metatranscriptomic analysis, we showed that some of these degradation genes are expressed in situ. Most of the bacterial isolates grew unhindered in the presence of PSCs and, using gas chromatography-mass spectrometry (GC-MS), we determined that isolates from the genera Bacillus, Burkholderia, Enterobacter, Klebsiella, and Pseudomonas degrade alfa-pinene, beta-caryophyllene, or linalool. Using a headspace sampler, we show that subcolonies of fungus gardens reduced alfa-pinene and linalool over a 36-h period, while L. gongylophorus strains alone reduced only linalool. Overall, our results reveal that the bacterial communities in fungus gardens play a pivotal role in alleviating the effect of PSCs on the leaf-cutter ant system.